Association Between Serum Iron Status and Muscle Mass in Adults: Results From NHANES 2015–2018 - Chen, Zhi; Chen, Jing; Song, Chenyang; Sun, Jun; Liu, Wenge (Frontiers in Nutrition, 2022)
Background: Iron deficiency or overload may contribute to complications associated with diseases, but the link between iron status and skeletal muscle disorder is poorly understood. This study aimed to investigate the relationship between serum iron status, reflected by serum ferritin concentration, and muscle mass in U.S. adults. Methods: We utilized data from National Health and Nutrition Examination Survey (NHANES) 2015-2018 for analysis. Data on serum ferritin, appendicular skeletal muscle mass (ASM), body mass index (BMI) and confounding factors were extracted and analyzed. Multivariate linear regression analyses and smooth curve fittings were employed to investigate the association between serum ferritin and muscle mass. Subgroup analysis based on iron status, age, gender and race were performed. Results: A total of 2078 participants were included, and divided into iron deficiency (n = 225), normal iron status (n = 1366), and iron overload (n = 487) groups. Participants with iron overload had significantly lower ASM and appendicular skeletal muscle index (ASMI) (ASM: 19.329 ± 4.879, ASMI: 0.709 ± 0.138) compared to those with iron deficiency (ASM: 22.660 ± 6.789, ASMI: 0.803 ± 0.206) and normal iron status (ASM: 22.235 ± 6.167, ASMI: 0.807 ± 0.201). The serum ferritin was negatively linked with muscle mass after adjusting for potential confounders (β = -0.0001, 95% CI: -0.0001, -0.0000). When stratified by iron status, the trend test between them remained significant (P for trend: 0.008). Furthermore, subgroup analysis identified a stronger association in men (β = -0.0001, 95% CI: -0.0002, -0.0001), age ≥ 40 years (β = -0.0001, 95% CI: -0.0002, -0.0000), non-Hispanic black (β = -0.0002, 95% CI: -0.0003, -0.0001) and other races (β = -0.0002, 95% CI: -0.0003, -0.0000). Conclusions: Our study revealed an inverse relationship between serum iron status and muscle mass in adults. This finding improves our understanding of the impact of serum iron status on muscle mass, and sheds new light on the prevention and treatment of muscle loss.